Effects of information quality and resource quality on product disclosure sheet quality among Malaysian Islamic banks - Muhammad Fakhirin, Che Majid (2021)
A Product Disclosure Sheet (PDS) is an important document that contains key information on financial products provided by Islamic banks to facilitate customers to compare products and make informed decisions. However, the PDS is less effective due poor quality with incomplete disclosure. In fact, empirical studies on PDS quality are limited. Therefore, the main purpose of this study was to examine the effects of information quality and resource quality on the PDS quality of Islamic banks in Malaysia. Specifically, the objectives of the study were to examine the influence of information quality and resource quality on PDS quality, and the moderating effect of information technology on that relationship. This study used quantitative methods and was based on information asymmetry and task-technology fit theories. A total of 754 questionnaires were collected via the convenience sampling technique. Data was analysed using the Partial Least Squares Structural Equation Modelling technique. The findings reveal that information quality (t=12.384, p=0.000) and resource quality (t=5.068, p=0.000) have significantly positive relationships with PDS quality. However, information technology does not moderate the relationship between information quality (t=1.869, p=0.073) and resource quality (t=1.807, p=0.060) and PDS quality. This study contributes to the body of knowledge on PDS quality and aspects of Islamic finance principles in order to prevent ambiguity (gharar). In terms of practical contributions, this study recommends reform practices for Islamic banks to improve the preparation and presentation of quality PDS to customers. It also contributes guidance to Bank Negara Malaysia as a policy-maker to leverage these findings to improve the existing policies, guidelines, and practices of providing quality PDS and conducting audits and supervision regularly to enhance the quality of PDS.